Subsurface water flow assessed with electrical resistivity and ground-penetrating radar in yachay tech, Ecuador - Arteaga Pozo, María Emilia (2019)
Water management plays an important role in supplying populations with clean water for agriculture, livestock and human consumption. Hence, investigation of the quality of aquifers, watercourses and their potential pollutants is important for communities all over the world. Here, we used electrical resistivity and ground-penetrating radar, which have been utilized successfully for water flow assessment, to evaluate a possibly contaminated open water-storage pool in an emerging city of Yachay in northern Ecuador. In this thesis we compared the subsurface electrical resistivity pseudosections with the radargrams and used physicochemical analysis of water to answer the following questions: (1) Is the water channelled to the pool or is the water channel broken, seeping and causing the vegetation patches around the pool? (2) How is the water flowing at the subsurface below and above the pool? (3) How is this flow being influenced by weather conditions? (4) Is the pool itself in good condition and retaining the water or is there leakage from the pool? (5) Is the water that is flowing through the channel contaminated by pollution or organic waste? The geophysical survey results from 2017 showed that the areas with low resistivity values and high reflectance match with the dense vegetation on the surface. This clearly showed that the channel to the pool was either blocked or broken, creating a distinct leakage pattern around the pool. After 2017 a small channel was dug to the pool again allowing the water to flow again. Monthly electrical resistivity measurements between October 2018 – February 2019 revealed that the subsurface water content shows fluctuations with areal precipitation. The physicochemical and biochemical analysis showed that the water flowing through the ditch is not suitable for human consumption due to its elevated content of BOD and coliforms. However, these values are below the lower limit of greywater and therefore the water is suitable for agriculture and livestock usage.